2022
DOI: 10.1186/s43042-022-00316-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs influence and longevity

Abstract: Background MiRNAs play critical roles in the regulation of cellular function, life span, and the aging process. They can affect longevity positively and negatively through different aging pathways. Main text MiRNAs are a group of short non-coding RNAs that regulate gene expressions at post-transcriptional levels. The different types of alterations in miRNAs biogenesis, mRNA expressions, and activities of miRNA-protein complexes can affect the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 179 publications
0
3
0
1
Order By: Relevance
“…MiRNAs are key modulators in maintaining tissue homeostasis by post-transcriptionally regulating gene expression. Thus, an imbalance in their expression has been associated with disease progression and aging-related cellular processes including senescence 44,45 . Here, we aimed to characterize miRNA gene transcription in single-cell datasets to study cell-type specific miRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are key modulators in maintaining tissue homeostasis by post-transcriptionally regulating gene expression. Thus, an imbalance in their expression has been associated with disease progression and aging-related cellular processes including senescence 44,45 . Here, we aimed to characterize miRNA gene transcription in single-cell datasets to study cell-type specific miRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that different miRNAs play a role in the regulation of age-related illnesses, including AD, age-related macular degeneration, neurological disorders, and cancer ( Natoli and Fernando, 2018 ; Eshkoor et al, 2022 ). Studies have shown that nutritional components and nutraceuticals can control the activity of miRNAs that have a role in age-related disorders.…”
Section: Implications For Prevention and Treatment Of Age-related Dis...mentioning
confidence: 99%
“…Numerous factors influence miRNA expression levels, including age (Eshkoor et al, 2022; Jin Jung & Suh, 2012), gender (Lin, Han, et al, 2022; Lin, Liu, et al, 2022; Lin, Wu, et al, 2022), lifestyle (Panico et al, 2021), and an individual's disease history (Li & Kowdley, 2012). Multiple factors collaboratively influence the expression level of miRNA.…”
Section: Summary and Future Perspectivementioning
confidence: 99%